Принцип контрольованості у системі контролінга центрів фінансової відповідальності - Парцирна, Алла Леонідівна (НТУ "ХПІ", 2014)
У статті узагальнено зарубіжний досвід щодо використання принципу контрольованості при оцінці діяльності центрів фінансової відповідальності. Автором проаналізовано доцільність використання контрольованих показників у системі контролінга внутрішньофірмових відносин. Досліджено сутність поняття принципу умовної контрольованості.

The article has summarized foreign experience regarding the application of a controllability principle while evaluating the activity of financial responsibility centers. The author has analyzed the appropriateness of using controllable indicators in the controlling system of intra-firm relations. The essence of the notion of conditional controllability has been investigated.
The controllability principle in the controlling system of financial responsibility centers
Keywords: умовна контрольованість; зарубіжний досвід; внутрішньофірмові відносини; controllability principle; conditional controllability; responsibility centers